2023
DOI: 10.1101/2023.02.01.526664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale high-density brain-wide neural recording in nonhuman primates

Abstract: High-density, integrated silicon electrodes have begun to transform systems neuroscience, by enabling large-scale neural population recordings with single cell resolution. Existing technologies, however, have provided limited functionality in nonhuman primate species such as macaques, which offer close models of human cognition and behavior. Here, we report the design, fabrication, and performance of Neuropixels 1.0-NHP, a high channel count linear electrode array designed to enable large-scale simultaneous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 68 publications
0
36
0
Order By: Relevance
“…Fig. 11) recorded from rhesus macaque using Neuropixels 1.0-NHP probes 33 . The probe was inserted from the motor cortex targeting globus pallidus internus (GPi) in the basal ganglia using a commercial drive system (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 11) recorded from rhesus macaque using Neuropixels 1.0-NHP probes 33 . The probe was inserted from the motor cortex targeting globus pallidus internus (GPi) in the basal ganglia using a commercial drive system (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The methods are described in detail elsewhere 33 , but, in brief, the Non-human primate recordings used the Neuropixels 1.0-NHP probe manufactured in two variants: 1) 45 mm long x 125 μm wide x 90 μm thick, featuring 4416 electrodes comprising 11.5 banks of 384 channels each; and 2) 25 mm long, 125 μm wide, and 60 μm thick, featuring 2496 electrodes comprising 6.5 banks of 384 channels with two aligned vertical columns. Probe tips were sharpened to a 25°angle using the Narishige EG-402 micropipette beveler.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (Jonikaitis et al, 2023), we identified the FEF based on its neurophysiological characteristics and the ability to evoke saccades with electrical stimulation. Here, we recorded from FEF and anterior sites (Broadmann areas 9/46) using primate neuropixels probes (Trautmann et al, 2023). We pierced the dura using a screw-driven 21 gauge pointed cannula and lowered the probe through this cannula using a combination of custom 3D printed grids and motorized drives (NAN instruments).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In the past several years, high-density, silicon probes, most notably Neuropixels probes (IMEC inc.), have revolutionized large-scale electrophysiological recordings in the mouse brain (Jun et al, 2017; Steinmetz et al, 2021). More recently, these probes were adapted for use in nonhuman primates (Trautmann et al, 2023). We used these newly developed probes to obtain recordings from large, dense populations of prefrontal neurons in monkeys performing the spatial working memory tasks (Fig.…”
Section: Introductionmentioning
confidence: 99%